Cooperative Learning Strategy Type Two Stay Two Stray (TSTS) in Muthola'ah Lesson - Muhaimin, Zaki Abdul (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2023)
Current trends in Arabic language learning involve the use of game-based strategies. One such strategy is the Two Stay Two Stray (TS-TS) strategy, which is a component of cooperative learning strategies aimed at encouraging students to explore the knowledge they desire. The Two Stay Two Stray (TS-TS) strategy requires a detailed design, as it is a crucial part of the teacher's task. This study is a literature review of the Two Stay Two Stray (TS-TS) strategy in learning, seeking its application format in Arabic language learning, specifically in Muthola’ah. Based on the existing literature review, there are not many designs and plans for implementing this strategy in Arabic language learning. One of the novelties of this research is the formulation of the TS-TS strategy design based on a literature review of various existing studies, integrated with the specificities of teaching Arabic, especially Muthola’ah, using the direct method applied at Walisongo Ngabar Islamic Boarding School in Ponorogo, East Java.